Monitoring air pollution effects on children for supporting public health policy: the protocol of the prospective cohort MAPEC study. Issue 9 (16th September 2014) - Feretti, D; Ceretti, E; De Donno, A; Moretti, M; Carducci, A; Bonetta, S; Marrese, M R; Bonetti, A; Covolo, L; Bagordo, F; Villarini, M; Verani, M; et al.
Abstract : Introduction: Genotoxic biomarkers have been studied largely in adult population, but few studies so far have investigated them in children exposed to air pollution. Children are a high-risk group as regards the health effects of air pollution and some studies suggest that early exposure during childhood can play an important role in the development of chronic diseases in adulthood. The objective of the project is to evaluate the associations between the concentration of urban air pollutants and biomarkers of early biological effect in children, and to propose a model for estimating the global risk of early biological effects due to air pollutants and other factors in children. Methods and analysis: Two biomarkers of early biological effects, DNA damage by the comet assay and the micronuclei (MN) test, will be investigated in oral mucosa cells of 6–8-year-old children. Concurrently, some toxic airborne pollutants (polycyclic aromatic hydrocarbon (PAH) and nitro-PAH) and in vitro air mutagenicity and toxicity in ultra-fine air particulates (PM0.5) will be evaluated. Furthermore, demographic and socioeconomic variables, other sources of exposures to air pollutants and lifestyle variables will be assessed by a structured questionnaire. The associations between sociodemographic, environmental and other exposure variables and biomarkers of early biological effect using univariate and multivariate models will be analysed. A tentative model for calculating the global absolute risk of having early biological effects caused by air pollution and other variables will be proposed. Ethics and dissemination: The project has been approved by the Ethics Committees of the local Health Authorities. The results will be communicated to local Public Health Agencies, for supporting educational programmes and health policy strategies. LIFE+2012 Environment Policy and Governance. LIFE12 ENV/IT/000614.